Advances in laser-induced graphene: materials, fabrication, and emerging applications in flexible electronics - Oh, In Jun; Kim, Doyoun; Kim, Seong-Yeop; Choi, Sueun; Yeo, Woon-Hong; Lim, Hyo-Ryoung (Frontiers in Nanotechnology, 2026)
Laser-induced graphene (LIG) has evolved from a rapid polymer-to-carbon conversion method into a versatile platform for fabricating high-performance flexible electronics. This review provides a comprehensive understanding of the photothermal and photochemical mechanisms governing LIG formation, emphasizing how laser parameters wavelength, fluence, and scanning speed determine graphitization pathways and resulting electrical characteristics. Beyond process fundamentals, we highlight recent advances in conductivity engineering achieved through pre- and post-treatment strategies, including metal nanoparticle incorporation, catalytic doping, and rapid Joule annealing. These modifications enable sheet resistances below 10 Ω/sq and significantly enhance electrochemical and mechanical performance. Finally, we discuss the integration of LIG in flexible sensors, energy harvesters, and bioelectronic systems, underscoring its scalability, design freedom, and environmental sustainability. By unifying insights across mechanism, processing, and application, this review outlines a coherent roadmap for harnessing LIG as a key material in next-generation soft electronics and wearable technologies.